Maternal awareness of newborn danger signs before discharge: a secondary analysis of baseline data from a quasi-experimental study in Uganda - Businge Alinaitwe; Francis Nkunzimaana; Charles Kato; Rachel Uwimbabazi; Petranilla Nakamya; Molly McCoy; Adam Kaplan; Elizabeth Ayebare; Jameel Winter; Tom Denis Ngabirano (Maternal Health, Neonatology and Perinatology)
Abstract Background The neonatal period is the most vulnerable time for children under 5 years. Neonatal mortality contributes to almost one-half of all under-5 deaths. Developing one or more newborn danger signs increases the mortality risk in the first 28 days of life. Understanding maternal awareness of newborn danger signs is essential in promoting early newborn care-seeking for better outcomes. In Uganda, there is a paucity of evidence on maternal awareness of newborn danger signs (NDS) immediately after delivery. This study aimed to determine the level and factors associated with maternal awareness of NDS before discharge from the hospital. Methods This is a secondary analysis of baseline data from a hospital-based enhanced maternal education intervention conducted at a Tertiary Care and Teaching Hospital in Eastern Uganda. Maternal awareness of NDS was assessed by recording spontaneous maternal responses to the question, ‘What are the danger signs of a newborn baby that you know? Women who mentioned ≥ 3 NDS were categorized as having a good awareness. Frequencies and percentages for all categorical variables were presented in tables and charts. Binary logistic regression analysis was used to determine the factors associated with awareness of NDS. Results The baseline survey enrolled 250 post-natal women. Only 14.0% of the participants had a good awareness of NDS. High body temperature/fever (73.6%) and poor breastfeeding/or failure to breastfeed (38.8%) were the commonly identified NDS. Hypothermia, cord sepsis (0.4%), skin pustules (1.6%), and convulsions (4.6%) were the least identified NDS. Mode of delivery (p = 0.039) and maternal age (p = 0.032) were significantly associated with maternal awareness of NDS. Conclusions Maternal awareness of newborn danger signs in the immediate post-delivery period is poor. The women do not know the majority of the NDS, and therefore, these signs can go undetected, delaying care-seeking and posing a risk for poor infant outcomes. Routine postnatal health education should focus on these danger signs while ensuring that younger mothers and women who deliver by cesarean section are given special attention during knowledge enhancement sessions.